2004
DOI: 10.1093/nar/gkh736
|View full text |Cite
|
Sign up to set email alerts
|

High salt solution structure of a left-handed RNA double helix

Abstract: Right-handed RNA duplexes of (CG)n sequence undergo salt-induced helicity reversal, forming left-handed RNA double helices (Z-RNA). In contrast to the thoroughly studied Z-DNA, no Z-RNA structure of natural origin is known. Here we report the NMR structure of a half-turn, left-handed RNA helix (CGCGCG)2 determined in 6 M NaClO4. This is the first nucleic acid motif determined at such high salt. Sequential assignments of non-exchangeable proton resonances of the Z-form were based on the hitherto unreported NOE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 40 publications
2
49
2
Order By: Relevance
“…S3L). We note that the helicity and elongation that we observe for L-RNA under torsional constraint are similar to what has been proposed for the NMR solution structure of a short (6-bp) GC-rich dsRNA fragment in 6 M monovalent salt (30). However, further investigation is necessary to elucidate structural details of torsionally strained left-handed dsRNA.…”
Section: Resultssupporting
confidence: 86%
“…S3L). We note that the helicity and elongation that we observe for L-RNA under torsional constraint are similar to what has been proposed for the NMR solution structure of a short (6-bp) GC-rich dsRNA fragment in 6 M monovalent salt (30). However, further investigation is necessary to elucidate structural details of torsionally strained left-handed dsRNA.…”
Section: Resultssupporting
confidence: 86%
“…It was shown by neutron diffraction that the salt ions induce a change in water structure equivalent to that of application of high pressure [29]. In RNA molecules, conformational changes were detected at 6 M NaClO 4 and 42 • C [30][31][32]. It has been shown experimentally and theoretically that water molecules, even located at long distances from the solute (>10Å), are structurally important [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The work of Davis et al, [18] and Popenda et al, [19] on the high salt structure of a left-handed RNA double helix is well-known. It was found that for the natural ribohexanucleotide r(C P G P C P G P C P G) at 1M concentration a duplex is formed with an A-conformation.…”
Section: Comparison With a Self-complementary Natural Rna And Its 2ꞌ-mentioning
confidence: 99%
“…For the role of dispersion interactions it is necessary to have at one's disposal a representative model for the solely duplex-and filling-space structures of the aforementioned (modified) DNA and RNA. For the antiparallel phosphate-methylated DNA there is a self-complementary left-handed dimer d(C P G) [4], its (right-handed) tetramer d(C P G P C P G) [14], and the right-handed r(2ꞌ-OMe)C P G [19] available. The individual duplex structures were obtained from CD and NMR data, vide supra.…”
Section: Bio-physical Characteristics Of Phosphate-methylated Dna Comentioning
confidence: 99%